Transformation of the Role of Android Smartphones: From Communication Devices to Remote Control for IoT Based Home Automation Systems - Sumaryanto, Agus; Diantoro, Karno; Rinaldo; Juwari (Indonesian Scientific Publication, 2023)
Smartphone technology, especially Android smartphones, has advanced quickly in terms of their function as smart and communication devices. Their capacity to function as remote control tools, enabling users to view and manage electronic gadgets via an Internet connection, is one notable advancement. Through the use of the Internet connection as a bridge between devices, smartphone-based remote control indirectly makes it easier to monitor and manage electrical gadgets. Uncontrolled electricity use and instances of high power consumption that occur when people forget to turn off equipment provide a challenge. The author suggests using the prototyping method, in which a prototype is created at the beginning stage for later development, to overcome this problem. Through